Re‐Evaluation of Low Cloud Amount Relationships With Lower‐Tropospheric Stability and Estimated Inversion Strength - Lauren Cutler; Michael A. Brunke; Xubin Zeng (Geophysical Research Letters)
Abstract Lower‐tropospheric stability (LTS) and estimated inversion strength (EIS) have a widely accepted relationship with low cloud amount and are key observational foundations for understanding and modeling low‐level stratiform clouds. Using the updated surface‐based and satellite cloud data, we find that low cloud amount is not as strongly correlated with LTS, and not as sensitive to LTS, as established in the past. EIS does not provide a stronger correlation with low cloud amount than LTS over all eight regions (including the midlatitudes). Further analyzing the relationships between LTS and EIS with different types of low clouds, we find that there is a strong correlation of LTS and EIS with stratocumulus only. This explains the weaker correlation of low cloud fraction (including cumulus, stratocumulus, and stratus) to both LTS and EIS. These results also suggest the need to re‐evaluate these relationships in Earth system models.